Integrating the coffee culture with the teaching of english (2009)
The present article gives account of the results of a research project developed at the University of Caldas with a group of preservice teachers and advisors. The purpose of the work was to sensitize the academic community about the importance of rescuing the cultural identity of rural school students. To achieve this goal, advisors and preservice teachers innovated the school curriculum by integrating the coffee culture to the English program. The study revealed that preservice teachers became skillful at designing content-based tasks that were more meaningful for the students; likewise, they became more sensitive to the problems that affected rural students and their families. It was also found that these students became aware of the commitment they had with the region and its surroundings; furthermore, because classes were more appealing, their motivation increased significantly. Key words: Cultural integration, curriculum, preservice teacher, foreign language teaching-learning process, rural school Este artículo da cuenta de los resultados de una investigación desarrollada en la Universidad de Caldas con un grupo de educadores en formación y sus asesoras, con el fin de sensibilizar a la comunidad académica sobre la importancia de rescatar la identidad cultural de los estudiantes de las escuelas rurales. Para lograr este objetivo, las asesoras y educadores en formación realizaron innovaciones en el currículo al integrar la cultura cafetera a los contenidos de los cursos de inglés. El estudio demostró que los docentes en formación desarrollaron habilidades para diseñar actividades que integraran los contenidos de inglés con la cultura cafetera y que fueran más significativas para los estudiantes. Asimismo, se mostraron más sensibles hacia los problemas que afectaban a los estudiantes y a sus familias. Se encontró también que los estudiantes de las escuelas rurales se concientizaron acerca del compromiso que debían tener con la región y sus alrededores. Puesto que las clases fueron más atractivas, los niveles de motivación de los estudiantes incrementaron significativamente. Palabras clave: Integración cultural, currículo, practicante, procesos de enseñanza-aprendizaje de una lengua extranjera, escuela rural